2016
DOI: 10.1021/acs.organomet.6b00519
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Ge–Ge and Sn–Sn Triple Bonds in Heavy Group 14 Element Alkyne Analogues (EAriPr4)2 (E = Ge, Sn; AriPr4 = C6H3-2,6(C6H3-2,6-iPr2)2) by Reaction with Group 6 Carbonyls

Abstract: The reactions of heavier group 14 element alkyne analogues (EAr iPr4 )2 (E = Ge, Sn; Ar iPr4 = C6H3-2,6-(C6H3-2,6-i Pr2)2) with the group 6 transition metal carbonyls M(CO)6 (M = Cr, Mo, W)under UV irradiation resulted in the cleavage of the E-E bond and the formation of complexes {Ar iPr4 EM(CO)4}2 (1-6) that were characterized by single crystal X-ray diffraction as well as by IR and multinuclear NMR spectroscopies. Single crystal X-ray structural analyses of 1-6 showed that the complexes have a nearly planar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…Similar Ge 2 M 2 rings can be found in the reaction of the digermyne [Ar Pri4 Ge] 2 (Ar Pri4 = 2,6-Ar 2 C 6 H 3 , Ar = 2,6-iPr 2 C 6 H 3 ) with M(CO) 6 (M = Cr, Mo, W) under UV irradiation to form [Ar Pri4 GeM(CO) 4 ] 2 , but the reaction mechanisms are unknown as of yet. 19 The Ge1 and Ge1A atoms, which adopt a distorted tetrahedral geometry, are coordinated with the bidentate 2-imino-5,6-methylenedioxylphenyl ligand and two manganese (Mn1 and Mn1A) atoms. The latter are also bonded to four CO moieties to adopt an octahedral geometry.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similar Ge 2 M 2 rings can be found in the reaction of the digermyne [Ar Pri4 Ge] 2 (Ar Pri4 = 2,6-Ar 2 C 6 H 3 , Ar = 2,6-iPr 2 C 6 H 3 ) with M(CO) 6 (M = Cr, Mo, W) under UV irradiation to form [Ar Pri4 GeM(CO) 4 ] 2 , but the reaction mechanisms are unknown as of yet. 19 The Ge1 and Ge1A atoms, which adopt a distorted tetrahedral geometry, are coordinated with the bidentate 2-imino-5,6-methylenedioxylphenyl ligand and two manganese (Mn1 and Mn1A) atoms. The latter are also bonded to four CO moieties to adopt an octahedral geometry.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This yields nonbonded electron density at the group 14 atoms which results in bending of the geometry via interelectronic repulsion and a change in the relative energies and symmetries of the frontier orbitals from π (HOMO) and π* (LUMO) in the linear form to a π (HOMO) and n + (LUMO) in the trans-bent configuration. 4 This allows matching of the symmetry of the frontier orbitals of the dimetallynes with those of several important small molecules such as H 2 5−7 and ethylene 8 and also facilitates reactions with other molecules such as cyclopentadiene 9 and metal carbonyls 10 under mild conditions to yield products in which the E−E bonds are broken. Thus, the bonding models in Scheme 1 and the observed reaction patterns suggest that the E−E triple bonds are relatively weak despite the fact that the Sn−Sn bond distance in Ar iPr4 SnSnAr iPr4 , 2.6675(4)Å, 2d is shorter than the sum (2.8 Å) 11 of the single-bond covalent radii of tin (cf.…”
mentioning
confidence: 99%
“…The green trace (b) is the Sn­(I) radical intermediate from by UV photolysis/thermolysis at 80 °C of Sn­(Ar i Pr4 ) 2 in benzene for ca. 30 min . Spectrometer settings: 15 K, 0.1 mW power (no saturation), microwave frequency, 9.38 GHz, conversion time, 40 ms, modulation amplitude, 0.8 mT, modulation frequency, 100 kHz.…”
mentioning
confidence: 99%
“…More recent work has shown that the above species can be synthesized by the metathesis of the dimetallynes REER (R = terphenyl; E = Ge, Sn, or Pb) with the single- or triple-bonded transition-metal species, (CO) 3 CpMo−MoCp­(CO) 3 or (CO) 2 CpMoMoCp­(CO) 2 , respectively . In addition, the distannyne and digermyne were reacted with the group six carbonyls M­(CO) 6 to form the cluster species {Ar i Pr 4 EM­(CO) 4 } 2 (E = Ge, Sn; Ar i Pr 4 = −C 6 H 3 –2,6-(C 6 H 3 –2,6- i Pr 3 ) 2 ) . However, the reactivity of diplumbynes toward simple transition metal carbonyls remains hardly explored.…”
Section: Introductionmentioning
confidence: 99%
“…. 20 However, the reactivity of diplumbynes toward simple transition metal carbonyls remains hardly explored. Herein, we report the syntheses and characterizations of metalloplumbylenes Mn(CO) 5 (PbAr ■ EXPERIMENTAL SECTION General Procedures.…”
Section: ■ Introductionmentioning
confidence: 99%